Early Childhood Education in Three Cultures: China, Japan and the United States - HUO, Liyan (Springer, 2016)
This book, written by an international team of experienced researchers, investigates unique and dynamic approaches to key issues in policy transformation, curriculum reforms and teacher training in three cultures – China, Japan and the United States – in a globalized world. By examining their respective policy choices and evidence-based practices, the authors show how best to provide for young children based on their needs and interests, and the three countries’ strategies for doing so. This book provides the latest information on the rapid developments already underway and further changes to be expected in these diverse cultures.